Poems - Wilde, Oscar (Saga Egmont, 2022)
‘Poems’ was published at Wilde’s expense less than 10 years before he wrote his acclaimed novel, ‘The Picture of Dorian Gray.’ It contains some of his best-loved poetry, including ‘Ravenna,’ ‘The Ballad of Reading Gaol,’ and ‘Sonnet On Hearing The Dies Irae Sung In The Sistine Chapel.’ Despite being criticised in the Press, ‘Poems’ sold out during its first run and further editions had to be printed in the same year. Wilde went on to gift copies of the book to assorted dignitaries, including Albert Edward, the then Prince of Wales. The anthology is an insightful exploration of human emotions and a landmark in his career. Oscar Wilde (1854 – 1900) was an Irish novelist, poet, playwright, and wit. He was an advocate of the Aesthetic movement, which extolled the virtues of art for the sake of art. During his career, Wilde wrote nine plays, including ‘The Importance of Being Earnest,’ ‘Lady Windermere’s Fan,’ and ‘A Woman of No Importance,’ many of which are still performed today. His only novel, ‘The Picture of Dorian Gray’ was adapted for the silver screen, in the film, ‘Dorian Gray,’ starring Ben Barnes and Colin Firth. In addition, Wilde wrote 43 poems, and seven essays. His life was the subject of a film, starring Stephen Fry.